Dual flapping foil system for propulsion and harnessing wave energy: A 2D parametric study for unaligned foil configurations. (1st November 2020) - Moreira, Diego; Mathias, Nuno; Morais, Tiago
Abstract: Dual flapping foil systems are a promising concept able to improve overall ship propulsion performance and recover wave energy, reducing fuel consumption and making maritime equipment eco-friendlier. In this context, the present article aims to present a 2D parametric study of a flapping foil system able to operate in two modes: energy harnessing and propulsion. First, a brief theoretical review is presented, followed by the numerical approach used and the validation tests performed. The main goal of the parametric study is to analyse how the out-of-phase configuration and the spacing inter-foils influence the results in terms of hydrodynamic coefficients and power output, when compared to the baseline (foils aligned). Implementing the cases using the κ − ω SST turbulence model, combined with the overset 6DOF approach for the foil motion from the commercial CFD tool ANSYS® Fluent®, it was possible to show that cases 1 & 2 (unaligned, spaced configuration) presented a better overall performance for the two operation modes. Highlights: Flapping foils are a concept that can improve overall ship performance. A dual foil system can operate in two modes: energy harnessing and propulsion. Unaligned configurations have proved to be beneficial to the system performance. When foils are closer, performance is only better in the energy harnessing mode.